Exploring Perspectives of Basic and Clinical Sciences Medical Students on Research - Naiyar, Iffat; Noor, Iffat; Najeeb, Wajeha; Aneeqa Chughati; Muhammad Abdullah Ehsan; Shehryar Arshid (Pakistan Armed Forces Medical Journal, 2024)
Objective: To identify and compare motivating factors and obstacles towards research among undergraduate medical students of basic and clinical sciences. Study Design: Cross sectional study. Place and Duration of Study: Combined Military Hospital, Kharian medical college, Pakistan Jun to Aug 2021. Methodology: This study involved 205 undergraduate medical students divided into two groups: basic sciences (1st, 2nd, and 3rd year) and clinical sciences (4th year). Data collection was done using a self-structured questionnaire based on a 5-point Likert scale. Ethical approval was obtained from the institutional review board (CKMC/IERB/AC-00119). Results: Out of the participants, 84(40.9%) were male and 151(59%) were female. 183(89.2%) were aged 18-22, and 22(10.7%) were aged 23-27. Distribution by year was as follows: 1st year 17%, 2nd year 20.9%, 3rd year 15.6%, and 4th year 46.3%. Approximately 40-50% of clinical sciences students supported making research mandatory from the first to the final year and introducing weightage in the final assessment, foster critical thinking and teamwork, compared to only 2-17% of basic sciences students. This significant difference highlights the need for early integration of research activities in the medical curriculum (p-value<0.001). 40-50% of undergraduate students in both clinical and basic sciences agreed that there is a lack of research culture, infrastructure, training funds, and time. The barriers did not show significant differences between the groups. Conclusion: Clinical students’ perception of research is much better than basic sciences.